Environmental management accounting : case studies in South-East Asian companies - Herzig, Christian (London : Routledge, 2012)
'Sustainable development will not happen without substantial contributions from and leading roles of companies and business organizations. This requires the provision of adequate information on corporate social and ecological impacts and performance. For the last decade, progress has been made in developing and adapting accounting mechanisms to these needs but significant work is still needed to tackle the problems associated with conventional accounting. Until recently, research on environmental management accounting (EMA) has concentrated on developed countries and on cost-benefit analysis of implementing individual EMA tools. Using a comparative case study design, this book seeks to redress the balance and improve the understanding of EMA in management decision-making in emerging countries, focussing specifically on South-East Asian companies. Drawing on 12 case studies, taken from a variety of industries, Environmental Management Accounting: Case Studies of South-East Asian Companies explores the relationship between decision situations and the motivation for, and barriers to, the application of clusters of EMA tools as well as the implementation process itself. This book will be useful to scholars interested in the environmental and sustainability management accounting research field and those considering specific approaches to EMA within emerging economies.'--Publisher's website.
Includes bibliographical references and index.
Keywords: Environmental auditing -- Southeast Asia -- Case studies; Agricultural industries -- Environmental aspects -- Southeast Asia; Industries -- Environmental aspects -- Southeast Asia